2011
DOI: 10.1186/1471-2334-11-294
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and prognostic features among children with acute encephalitis syndrome in Nepal; a retrospective study

Abstract: BackgroundAcute encephalitis syndrome (AES) is commonly seen among hospitalized Nepali children. Japanese Encephalitis (JE) accounts for approximately one-quarter of cases. Although poor prognostic features for JE have been identified, and guide management, relatively little is reported on the remaining three-quarters of AES cases.MethodsChildren with AES (n = 225) were identified through admission records from two hospitals in Kathmandu between 2006 and 2008. Patients without available lumbar puncture results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 19 publications
2
33
1
Order By: Relevance
“…JEV is endemic in the Terai (southern) region of Nepal [Figure 1] and in the densely populated Kathmandu valley131531. JEV rarely infects adults living in endemic regions presumably because of exposure to virus during childhood and subsequent immunity32.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…JEV is endemic in the Terai (southern) region of Nepal [Figure 1] and in the densely populated Kathmandu valley131531. JEV rarely infects adults living in endemic regions presumably because of exposure to virus during childhood and subsequent immunity32.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies have relied on JEV confirmation primarily by single serum serology in the context of an encephalitic illness which may potentially overestimate the disease burden in an endemic setting. Previous hospital-based studies in Nepalese children have shown S. pneumoniae and H. influenzae type b as the most common bacterial pathogens and JEV as the major viral pathogen for CNS infections13141516. However, the etiology of encephalitis apart from JEV and the pathogens involved in CNS infections in adults remain unknown.…”
mentioning
confidence: 99%
“…25,26 Our study carefully included a group of patients who were at least 24 months post HSCT with a low risk of immature immune recovery, had discontinued any immunosuppressive agents at least 6 months prior to the study, and were without any clinical or laboratory evidence of chronic GVHD. Our data revealed that these patients had total lymphocyte and CD4+ cell counts of 41000 and 400 cells/mm 3 , respectively. We demonstrated that there were no serious adverse reactions to the JE vaccine (SA 14-14-2) in our patients.…”
Section: Discussionmentioning
confidence: 94%
“…Approximately half of the patients with JE suffer from long-term neurological deficits or death. 3 Immunization against JE virus is the most effective strategy for preventing JE infection. After the JE immunization program was implemented in Nepal, the incidence of JE was dramatically decreased.…”
Section: Introductionmentioning
confidence: 99%
“…These clinical findings represent the patient has acute inflammation of the brain and are used by clinicians to identify patients with acute encephalitis. Acute encephalitis can be related with severe complications, including seizures, limb paresis, impaired consciousness or death4567). Biomarker of neuronal damage in intracranial infection is importance to recognize to predict outcome and disease severity.…”
Section: Introductionmentioning
confidence: 99%